Computed Tomography Aortic Valve Calcium Scoring in Patients With Aortic Stenosis. (March 2018) - Pawade, Tania; Clavel, Marie-Annick; Tribouilloy, Christophe; Dreyfus, Julien; Mathieu, Tiffany; Tastet, Lionel; Renard, Cedric; Gun, Mesut; Jenkins, William Steven Arthur; Macron, Laurent; Sechrist, Jacob W.; Lacomis, Joan M.; et al.
Abstract : Background—: Computed tomography aortic valve calcium scoring (CT-AVC) holds promise for the assessment of patients with aortic stenosis (AS). We sought to establish the clinical utility of CT-AVC in an international multicenter cohort of patients. Methods and Results—: Patients with AS who underwent ECG-gated CT-AVC within 3 months of echocardiography were entered into an international, multicenter, observational registry. Optimal CT-AVC thresholds for diagnosing severe AS were determined in patients with concordant echocardiographic assessments, before being used to arbitrate disease severity in those with discordant measurements. In patients with long-term follow-up, we assessed whether CT-AVC thresholds predicted aortic valve replacement and death. In 918 patients from 8 centers (age, 77±10 years; 60% men; peak velocity, 3.88±0.90 m/s), 708 (77%) patients had concordant echocardiographic assessments, in whom CT-AVC provided excellent discrimination for severe AS (C statistic: women 0.92, men 0.89). Our optimal sex-specific CT-AVC thresholds (women 1377 Agatston unit and men 2062 Agatston unit) were nearly identical to those previously reported (women 1274 Agatston unit and men 2065 Agatston unit). Clinical outcomes were available in 215 patients (follow-up 1029 [126–2251] days). Sex-specific CT-AVC thresholds independently predicted aortic valve replacement and death (hazard ratio, 3.90 [95% confidence interval, 2.19–6.78]; P <0.001) after adjustment for age, sex, peak velocity, and aortic valve area. Among 210 (23%) patients with discordant echocardiographic assessments, there was considerable heterogeneity in CT-AVC scores, which again were an independent predictor of clinical outcomes (hazard ratio, 3.67 [95% confidence interval, 1.39–9.73]; P =0.010). Conclusions—: Sex-specific CT-AVC thresholds accurately identify severe AS and provide powerful prognostic information. These findings support their integration into routine clinical practice. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT01358513, NCT02132026, NCT00338676, NCT00647088, NCT01679431. Abstract : Supplemental Digital Content is available in the text.